Improving provider-initiated testing for HIV and other STI in the primary care setting in Amsterdam, the Netherlands: Results from a multifaceted, educational intervention programme. - Saskia Bogers; Maarten Schim van der Loeff; Anders Boyd; Nynke van Dijk; Suzanne Geerlings; Jan van Bergen; HIV Transmission Elimination AMsterdam (H-TEAM) Consortium (PLoS ONE, 2023)
Background In the Netherlands, general practitioners (GPs) play a key role in HIV testing. However, the proportion of people diagnosed with late-stage HIV remains high, and opportunities for earlier diagnosis are being missed. We implemented an educational intervention to improve HIV and STI testing in primary care in Amsterdam, the Netherlands. Methods GPs were invited to participate in an educational program between 2015 and 2020, which included repeat sessions using audit and feedback and quality improvement plans. Data on HIV, chlamydia and gonorrhoea testing by GPs were collected from 2011 through 2020. The primary outcome was HIV testing frequency, which was compared between GPs before and after participation using Poisson regression. Secondary outcomes were chlamydia and gonorrhoea testing frequencies, and positive test proportions. Additional analyses stratified by patient sex and age were done. Findings GPs after participation performed 7% more HIV tests compared to GPs before participation (adjusted relative ratio [aRR] 1.07, 95%CI 1.04-1.09); there was no change in the proportion HIV positive tests (aRR 0.87, 95%CI 0.63-1.19). HIV testing increased most among patients who were female and ≤19 or 50-64 years old. After participation, HIV testing continued to increase (aRR 1.02 per quarter, 95%CI 1.01-1.02). Chlamydia testing by GPs after participation increased by 6% (aRR 1.06, 95%CI 1.05-1.08), while gonorrhoea testing decreased by 2% (aRR 0.98, 95%CI 0.97-0.99). We observed increases specifically in extragenital chlamydia and gonorrhoea testing. Conclusions The intervention was associated with a modest increase in HIV testing among GPs after participation, while the proportion positive HIV tests remained stable. Our results suggest that the intervention yielded a sustained effect.